Control of cytoplasmic and nuclear protein kinase A by phosphodiesterases and phosphatases in cardiac myocytes. (18th February 2014) - Haj Slimane, Zeineb; Bedioune, Ibrahim; Lechêne, Patrick; Varin, Audrey; Lefebvre, Florence; Mateo, Philippe; Domergue-Dupont, Valérie; Dewenter, Matthias; Richter, Wito; Conti, Marco; El-Armouche, Ali; Zhang, Jin; et al.
Abstract: Aims: The cAMP-dependent protein kinase (PKA) mediates β-adrenoceptor (β-AR) regulation of cardiac contraction and gene expression. Whereas PKA activity is well characterized in various subcellular compartments of adult cardiomyocytes, its regulation in the nucleus remains largely unknown. The aim of the present study was to compare the modalities of PKA regulation in the cytoplasm and nucleus of cardiomyocytes. Methods and results: Cytoplasmic and nuclear cAMP and PKA activity were measured with targeted fluorescence resonance energy transfer probes in adult rat ventricular myocytes. β-AR stimulation with isoprenaline (Iso) led to fast cAMP elevation in both compartments, whereas PKA activity was fast in the cytoplasm but markedly slower in the nucleus. Iso was also more potent and efficient in activating cytoplasmic than nuclear PKA. Similar slow kinetics of nuclear PKA activation was observed upon adenylyl cyclase activation with L-858051 or phosphodiesterase (PDE) inhibition with 3-isobutyl-1-methylxantine. Consistently, pulse stimulation with Iso (15 s) maximally induced PKA and myosin-binding protein C phosphorylation in the cytoplasm, but marginally activated PKA and cAMP response element-binding protein phosphorylation in the nucleus. Inhibition of PDE4 or ablation of the Pde4d gene in mice prolonged cytoplasmic PKA activation and enhanced nuclear PKA responses. In the cytoplasm, phosphatase 1 (PP1) and 2A (PP2A) contributed to the termination of PKA responses, whereas only PP1 played a role in the nucleus. Conclusion: Our study reveals a differential integration of cytoplasmic and nuclear PKA responses to β-AR stimulation in cardiac myocytes. This may have important implications in the physiological and pathological hypertrophic response to β-AR stimulation.